Novel electrolytic copper foil and preparation method thereof, negative pole piece and secondary battery
By setting up a through-hole array on the surface of the copper layer of the electrolytic copper foil, the problem of poor lithium ion conduction of traditional copper foil in solid-state batteries is solved, achieving higher battery performance and energy density.
Patent Information
- Application Number
- CN202411288261.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional electrolytic copper foils are difficult to effectively conduct lithium ions in solid-state batteries, resulting in poor battery performance.
A new type of electrolytic copper foil is designed. The surface of the copper layer is equipped with a hole array. By adjusting the ranking and size of the pores, the infiltration of the electrolyte and the transmission efficiency of the lithium ion.
The adhesion between the negative electrode material and the copper foil is improved, the transmission efficiency of lithium ions is improved, the energy density and cycle life of the battery are enhanced, and the internal impedance of the battery is reduced.
Smart Images

Figure CN119361716A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a novel electrolytic copper foil and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art
[0002] In recent years, the sales volume of new energy vehicles in China has been gradually increasing every year, and power batteries are an indispensable core component of new energy vehicles. The power batteries currently used are basically liquid lithium-ion batteries, but the energy density of liquid lithium-ion batteries has approached the upper limit, and it is difficult to make a big breakthrough. Solid-state batteries are the next generation solution to replace liquid lithium-ion batteries. The difference from liquid lithium-ion batteries is that solid-state batteries use solid electrolytes instead of liquid electrolytes. Further subdivided, according to the content of the electrolyte, solid-state batteries can be divided into semi-solid batteries and all-solid-state batteries. Semi-solid batteries contain some electrolytes, and the electrolyte content is generally between 5% and 10%. All-solid-state batteries refer to electrolytes that are all solid and do not contain liquid electrolytes. Semi-solid batteries are the intermediate transition state from liquid batteries to all-solid-state batteries. Generally, "10% of the liquid in the battery" is used as the dividing line between semi-solid batteries and liquid batteries. At present, semi-solid batteries are gradually being commercialized. The transformation from liquid batteries to solid-state batteries is a major trend in the development of battery technology in the long run. There are two factors driving the transformation from liquid batteries to solid-state batteries: solid-state batteries have higher safety and energy density. Safety is a short-term driving factor, and energy density is a medium- and long-term driving factor.
[0003] As the current collector of the negative electrode material of lithium batteries, electrolytic copper foil is an important component of the electrode structure in lithium-ion batteries. It not only acts as a carrier of the negative electrode active material in the battery, but also plays the role of collecting and transmitting current, which has a great impact on the internal resistance and cycle performance of lithium-ion batteries. In solid-state batteries, since the electrolytes are all solid, the conduction process of lithium ions is more complicated. Conventional double-sided copper foil is difficult to meet the characteristics of solid-state batteries, so a special copper foil needs to be specially designed to match solid-state batteries. Summary of the invention
[0004] The present application provides a novel electrolytic copper foil and a preparation method thereof, a negative electrode plate and a secondary battery, the purpose of which is to improve the lithium ion conduction problem of traditional electrolytic copper foil and improve the performance of secondary batteries.
[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a novel electrolytic copper foil, comprising at least one copper layer, wherein at least part of the surface of the copper layer is provided with a through-hole array, wherein the through-hole array is formed by M*N through-holes arranged in M rows and N columns, M≥1, N≥1, M and N are both positive integers, each row of through-holes in the through-hole array is arranged along the x-direction, each column of through-holes in the through-hole array is arranged along the y-direction, the x-direction intersects with the y-direction and is located in the same plane, the thickness direction along the copper layer is the z-direction, and the z-direction is perpendicular to both the x-direction and the y-direction;
[0006] The thickness of the copper layer is recorded as h, the longest distance from the center point of the through hole to the edge of the through hole is the major semi-axis distance, and its length is recorded as a, the shortest distance from the center point of the through hole to the edge of the through hole is the minor semi-axis distance, and its length is recorded as b, the shortest vertical distance between adjacent through holes along the x direction is recorded as A, and the shortest vertical distance between adjacent through holes along the Y direction is recorded as B, the Y direction is perpendicular to the x direction, the surface area of the copper layer covered by the through hole array is the array area, and the surface area of the copper layer not covered by the through hole array is the non-array area, and the weight of the array area per square meter is recorded as m, then:
[0007]
[0008] Wherein, k is any value between 0.9 and 1.1.
[0009] Therefore, the electrolytic copper foil provided in the present application can improve the peeling strength of the active material on the copper foil, improve its adhesion during the charge and discharge process, and improve the wettability of the electrolyte, thereby improving the transmission efficiency of lithium ions, effectively solving the lithium ion conduction problem of traditional copper foil in solid-state batteries, and as a battery negative electrode current collector, it can effectively improve the performance of the battery, especially the solid-state battery.
[0010] In any embodiment of the present application, A is 200-2000 μm, and can be optionally 400-1500 μm, and / or B is 200-2000 μm, and can be optionally 400-1500 μm.
[0011] In any embodiment of the present application, a is 100-1500 μm, and can be optionally 200-1000 μm, and / or b is 100-1500 μm, and can be optionally 200-1000 μm.
[0012] In any embodiment of the present application, the porosity of the array region is 5%-50%, and can be optionally 10%-40%.
[0013] In any embodiment of the present application, the through hole array is arranged in a rectangular array and / or a diamond array.
[0014] In any embodiment of the present application, the through hole is circular and / or elliptical.
[0015] In any embodiment of the present application, the copper layer has two surfaces opposite to each other in its own thickness direction, namely a first surface and a second surface, and the surface roughness and / or brightness of the first surface and the second surface are different.
[0016] In any embodiment of the present application, the thickness of the copper layer is 3 μm-15 μm.
[0017] In any embodiment of the present application, the tensile strength of the electrolytic copper foil at room temperature is 15 kgf / mm 2 -30kgf / mm 2 The tensile strength of the non-array area of the copper layer at room temperature is 30kgf / mm 2 -70kgf / mm 2 , the room temperature is 25±5℃.
[0018] A second aspect of the present application provides a method for preparing an electrolytic copper foil, comprising the following steps:
[0019] The anode and the cathode to be plated are placed in an electrolyte for electrolysis to obtain an electrolytic copper foil, wherein the cathode has electrically insulating shielding points arranged in an array.
[0020] In any embodiment of the present application, the electrolyte comprises copper ions, sulfuric acid, halogen ions and organic additives;
[0021] Optionally, the concentration of the copper ions in the electrolyte is 70 g / L-130 g / L;
[0022] Optionally, the concentration of sulfuric acid in the electrolyte is 80 g / L-150 g / L;
[0023] Optionally, the concentration of the chloride ions in the electrolyte is 15 mg / L-50 mg / L;
[0024] Optionally, the concentration of the organic additive in the electrolyte is 20 mg / L-500 mg / L.
[0025] In any embodiment of the present application, the organic additives include a leveling agent, a brightener and a wetting agent.
[0026] The leveler is a nitrogen-containing compound, optionally including one or more of collagen, gelatin, thiourea, allylthiourea, ethylenethiourea and 2-amino-4-methylbenzothiazole, and optionally the mass concentration of the leveler in the electrolyte is 0.1 mg / L-40 mg / L; and / or,
[0027] The brightener is an organic divalent sulfide, optionally including one or more of sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium 3-(benzothiazole-2-mercapto) propane sulfonate and isothiourea propane sulfonic acid inner salt, and optionally the mass concentration of the brightener in the electrolyte is 0.1 mg / L-400 mg / L; and / or,
[0028] The wetting agent is a polyether compound, optionally including one or more of polyethylene glycol, hydroxyethyl cellulose, polypropylene glycol, allyl polyethylene glycol, and fatty amine polyoxyethylene ether. Optionally, the mass concentration of the wetting agent in the electrolyte is 1 mg / L-40 mg / L.
[0029] In any embodiment of the present application, the temperature of the electrolyte during the electrolysis process is 45°C-60°C.
[0030] A third aspect of the present application provides a negative electrode plate, comprising the electrolytic copper foil described above or the electrolytic copper foil prepared by the described method.
[0031] A fourth aspect of the present application provides a secondary battery, comprising the negative electrode plate.
[0032] In any embodiment of the present application, the secondary battery is a liquid, semi-solid or solid battery.
[0033] A fifth aspect of the present application provides an electrical device comprising at least one of the secondary batteries described above.
[0034] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.
[0035] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0037] Figure 1 It is a schematic diagram of the arrangement of a rectangular array;
[0038] Figure 2 Schematic diagram of the arrangement of the diamond array;
[0039] Figure 3 This is a SEM image of the array area of the electrolytic copper foil prepared in Example 1 of the present application;
[0040] Figure 4 This is a photo of the finished roll sample of the electrolytic copper foil prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0041] Below, some embodiments of the novel electrolytic copper foil and its preparation method, negative electrode plate, secondary battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0042] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0043] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0046] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0047] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0048] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0049] In solid-state batteries, traditional copper foil is used as the current collector. The adhesion between traditional copper foil and negative electrode active materials is low, and the wettability of the electrolyte on the electrode surface is poor, which leads to lithium ion conduction problems.
[0050] Based on this, the first aspect of the present application provides a new type of electrolytic copper foil, including at least one copper layer. The copper layer is provided with a through-hole array on at least part of its surface. The through-hole array is formed by M*N through-holes arranged in M rows and N columns, M≥1, N≥1, M and N are both positive integers, each row of through-holes in the through-hole array is arranged along the x direction, each column of through-holes in the through-hole array is arranged along the y direction, the x direction intersects with the y direction and is located in the same plane, the thickness direction along the copper layer is the z direction, and the z direction is perpendicular to both the x direction and the y direction.
[0051] The thickness of the copper layer is recorded as h, the longest distance from the center point of the through hole to the edge of the through hole is the major semi-axis distance, and its length is recorded as a, the shortest distance from the center point of the through hole to the edge of the through hole is the minor semi-axis distance, and its length is recorded as b, the shortest vertical distance between adjacent through holes along the x direction is recorded as A, and the shortest vertical distance between adjacent through holes along the Y direction is recorded as B, the Y direction is perpendicular to the x direction, the surface area of the copper layer covered by the through hole array is the array area, and the surface area of the copper layer not covered by the through hole array is the non-array area, and the weight of the array area per square meter is recorded as m, then:
[0052]
[0053] Wherein, k is any value between 0.9 and 1.1.
[0054] After the above-mentioned electrolytic copper foil is coated with the negative electrode material, the through holes will be filled with the negative electrode material, thereby improving the anti-peeling strength of the negative electrode material on the copper foil. The through-hole structure of the copper foil helps to improve the wettability of the electrolyte on the electrode surface, thereby improving the transmission efficiency of lithium ions. Especially in solid-state batteries, the above-mentioned electrolytic copper foil is used as a current collector for the negative electrode. It can not only collect current, but also form a good interface in the solid electrolyte, thereby effectively transmitting current. Good interface properties can reduce the energy loss of the battery during the charging and discharging process, and improve the energy density and cycle life of the battery. In addition, the above-mentioned electrolytic copper foil can also reduce the impedance inside the battery and further improve the charging and discharging performance of the battery. Compared with traditional copper foil, the above-mentioned electrolytic copper foil will be lighter (weight reduction can reach 20%) at the same specifications and sizes, which will reduce the weight proportion of copper foil in the battery module and improve the battery energy density. The above-mentioned electrolytic copper foil can also reduce the battery aging time and the amount of electrolyte used, and improve battery safety.
[0055] A through-hole array refers to a through-hole structure in which the center points are arranged in an array. In some embodiments, the through-holes in the through-hole array are circular and / or elliptical. For circular through-holes, the center points are arranged in an array, and in fact, the circular holes are also arranged in an array, and the arrangement of the two is consistent; for elliptical through-holes, by rotating with the center point as the base point, the arrangement of the major axis or minor axis in different directions can be obtained. The difference in direction may present that the through-holes are not arranged in an array. Therefore, the through-hole array of this application is based on the arrangement of the center point.
[0056] In some embodiments, the through hole array is arranged in a rectangular array. Figure 1 As shown, the through hole array is arranged in a rectangular array, and the x direction is perpendicular to the y direction. In this embodiment, the y direction is the same as the y direction. The longest distance from the center point of the through hole to the edge of the through hole is the long semi-axis distance, whose length is a, and the shortest distance from the center point of the through hole to the edge of the through hole is the short semi-axis distance, whose length is b. The shortest vertical distance between adjacent through holes along the x direction is A, and the shortest vertical distance between adjacent through holes along the Y direction is B. The electrolytic copper foil with through hole array arranged in a rectangular array has basically similar surface density per unit area in different regions. When stretched by winding tension, the force distribution is uniform, and the array area is not easy to deform or wrinkle.
[0057] In some embodiments, the through hole array is arranged in a diamond array, such as Figure 2 As shown, the through hole array is arranged in a diamond array, the x direction intersects with the y direction at a certain angle but is not perpendicular, and the x direction is perpendicular to the Y direction. In this embodiment, the Y direction and the y direction are different. The longest distance from the center point of the through hole to the edge of the through hole is the major semi-axis distance, whose length is a, and the shortest distance from the center point of the through hole to the edge of the through hole is the minor semi-axis distance, whose length is b. The shortest vertical distance between adjacent through holes along the x direction is A, and the shortest vertical distance between adjacent through holes along the Y direction is B.
[0058] In some embodiments, A is 200-2000 μm and any value therebetween or a range of any two numerical values, for example, 500 μm, 600 μm, 700 μm, 800 μm, 1000 μm, 1200 μm, 1400 μm, 1600 μm, 1800 μm. Further, A can be selected to be 400-1500 μm.
[0059] In some embodiments, B is 200-2000 μm and any value therebetween or a range of any two numerical values, for example, 500 μm, 600 μm, 700 μm, 800 μm, 1000 μm, 1200 μm, 1400 μm, 1600 μm, 1800 μm. Further, B can be selected to be 400-1500 μm.
[0060] In some embodiments, a is 100-1500 μm and any value therebetween or a range of any two numerical values, for example, it can also be 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1100 μm, 1200 μm, 1300 μm, 1400 μm. Furthermore, a can be optionally 200-1000 μm.
[0061] In some embodiments, b is 100-1500 μm and any value therebetween or a range of any two numerical values, for example, it can also be 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1100 μm, 1200 μm, 1300 μm, 1400 μm. Further, b can be optionally 200-1000 μm.
[0062] It should be further explained that the array area includes the through holes and the copper layer area between adjacent through holes, and the non-array area is the remaining copper layer area.
[0063] In some embodiments, the porosity of the array area is 5%-50% and any value therebetween or a range of any two numerical values, for example, it can also be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and can further be 10-40%.
[0064] The porosity of the array area is defined as the ratio of the through-hole area of the copper layer to the unit area per unit area. When the porosity of the array area is within the above range, the performance of the electrolytic copper foil as a negative electrode current collector is better. When the porosity is greater than 50%, the through holes are densely distributed on the copper layer, and the intervals between adjacent through holes are small, and the electrolytic copper foil is prone to folding or breaking during the winding process. When the porosity is less than 5%, when the electrolytic copper foil is used as a negative electrode current collector, the adhesion between the negative electrode active material and the electrolytic copper foil is relatively poor and easy to fall off, resulting in poor application of the electrolytic copper foil at the battery end.
[0065] The thickness of the copper layer has a well-known meaning in the art and can be measured by methods well-known in the art, such as using a weighing method to obtain the copper layer surface density, and then deriving the copper layer thickness from the copper layer surface density.
[0066] In some embodiments, the thickness of the copper layer is 3 μm-15 μm and any value therebetween or a range between any two values. It is understandable that the thickness of the copper layer can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm. The copper layer thickness within this range can further increase the capacity of the battery.
[0067] In some embodiments, there are two surfaces opposite to each other in the thickness direction, namely, a first surface and a second surface, and the surface roughness and / or brightness of the first surface and the second surface are different. It can be understood that the vertical distance between the first surface and the second surface is the thickness of the copper layer.
[0068] In some embodiments, the electrolytic copper foil further comprises at least one protective layer. Optionally, the protective layer comprises a first protective layer and a second protective layer, the first protective layer being disposed on the first surface, and the second protective layer being disposed on the second surface. The provision of the protective layer can effectively reduce oxidation on the surface of the electrolytic copper foil.
[0069] In some embodiments, the protective layer comprises at least one of chromium, glucose and nitride.
[0070] In some embodiments, the protective layer contains chromium. Further optionally, the content of chromium in the at least one protective layer is 20ppm to 80ppm and any value therebetween or a range between two values, for example, 30ppm, 40ppm, 50ppm, 60ppm, or 70ppm.
[0071] In some embodiments, the thickness of the first protective layer is 100nm to 300nm, and / or the thickness of the second protective layer is 100nm to 300nm. It is understandable that the thickness of the first protective layer can be independently selected from 100nm to 300nm and any value therebetween or a range between two values, for example, it can also be selected from 150nm, 200nm, 250nm; the thickness of the second protective layer can be independently selected from 100nm to 300nm and any value therebetween or a range between two values, for example, it can also be selected from 150nm, 200nm, 250nm.
[0072] In some embodiments, the tensile strength of the array region of the copper layer at room temperature is 15 kgf / mm 2 -30kgf / mm 2 And any value between them or a range between two values, for example, it can also be 16kgf / mm 2 、18kgf / mm 2 、20kgf / mm 2 、22kgf / mm 2 , 25kgf / mm 2 、28kgf / mm 2 The room temperature is 25±5°C.
[0073] The tensile strength of the array area is within this range. The electrolytic copper foil has better mechanical strength. The tensile strength of the array area is less than 15kgf / mm 2Electrolytic copper foil is easy to break under the action of tension, and when making the negative electrode of the battery, the electrolytic copper foil is also easy to break under the action of extrusion. The tensile strength of the array area is greater than 30kgf / mm 2 There are a large number of through holes in the electrolytic copper foil. Under the external force, the force-bearing area becomes smaller, and fracture is prone to occur in the edge area of the through hole.
[0074] In some embodiments, the tensile strength of the non-array region of the copper layer at room temperature is 30 kgf / mm 2 -70kgf / mm 2 And any value between them or a range between two values, for example, it can also be 35kgf / mm 2 、40kgf / mm 2 、45kgf / mm 2 、50kgf / mm 2 、55kgf / mm 2 、60kgf / mm 2 、65kgf / mm 2 The room temperature is 25±5°C. The electrolytic copper foil has better mechanical strength when the tensile strength of the non-array area is within this range.
[0075] The second aspect of the present application provides a method for preparing an electrolytic copper foil, comprising the following steps:
[0076] The anode and the cathode to be plated are placed in an electrolyte for electrolysis to obtain an electrolytic copper foil, wherein the cathode has electrically insulating shielding points arranged in an array.
[0077] The above method is a one-step forming method. The so-called one-step forming method means that during the electrolysis process, the copper foil will produce a porous structure in the corresponding area, and no post-processing is required. In the existing mature electrolytic copper foil process, the copper foil produced is generally non-porous copper foil. To achieve porous copper foil, the non-porous copper foil needs to be post-processed, such as mechanical drilling, chemical corrosion, electrochemical corrosion, and laser drilling, etc., which cannot be achieved in one step.
[0078] The principle of the above method is as follows: in the electrolytic copper foil system, the cathode roller acts as the cathode, and the electrons flow or migrate on the surface of the cathode roller. The copper ions in the electrolyte migrate to the surface of the cathode roller under the action of the anode and cathode electric fields and the liquid flow rate. The electrons flowing on the surface of the cathode roller are transferred to the copper ions close to the cathode roller. The copper ions obtain an electron to form cuprous ions. The cuprous ions continue to obtain an electron from the surface of the cathode roller to form copper atoms. Finally, the copper atoms are fixed on the surface of the cathode roller and gradually accumulated to form a copper foil of a certain thickness. Therefore, the cathode roller area immersed in the electrolyte will be completely covered by the electrolytic copper foil. The electrical insulation shielding point adopts a polymer material with high volume resistivity, which has excellent electrical insulation properties and can isolate the charged part from the uncharged part, so that the current acts in the specified area. Electrically insulating shielding points are prepared on the surface of the cathode roller. During the electrolysis process, although electrons pass through the shielded area of the cathode roller, the electrons in this area cannot be received by the copper ions in the electrolyte because the surface is covered by the electrically insulating shielding points. The electrons can only migrate or flow to the area without electrically insulating shielding to react with copper ions to form copper foil, while the area shielded by electrical insulation cannot generate copper foil through electrolysis, and ultimately through holes are formed in the copper foil.
[0079] In some embodiments, the electrically insulating shielding point adopts a volume resistivity greater than 10 9 Ω·cm organic polymer material. Without particular limitation, the electrical insulating shielding materials used include, but are not limited to, UV curing materials, heat curing materials and moisture curing materials. These materials exist in liquid form in the initial state, and after UV curing, heat curing or moisture curing, the material form changes from liquid to solid. The UV curing material has acrylate groups and / or epoxy groups. Under the irradiation of UV light with a certain energy density, the acrylate groups or epoxy groups react to form a three-dimensional network polymer material. Thermosetting materials are three-dimensional network polymer materials formed by active groups under the action of initiators or crosslinking agents under the action of high temperature. Moisture curing is a process in which the active functional groups in the material capture water molecules in the air to undergo condensation polymerization to form a three-dimensional network polymer material.
[0080] The distribution of the electrically insulating shielding points on the cathode roller is the same as the distribution of the through hole array on the electrolytic copper foil.
[0081] The preparation method of the electrically insulating shielding point can adopt the template method or the direct molding method. The template method uses tape to prepare, and the tape is punched according to the required through-hole array arrangement, and then the tape is adhered to the surface of the cathode roller, and then the shielding material is fully coated inside the through-holes of the tape. After the shielding material is coated, the tape is torn off, and the shielding material inside the through-holes of the tape remains on the surface of the cathode roller. Finally, the shielding material is cured to complete the preparation of the shielding point. The direct molding method uses automated equipment, through automated program settings, and automatic dispensing to directly prepare shielding points on the surface of the cathode roller. The shielding points can be cured during the automatic dispensing process.
[0082] In some embodiments, the concentration of copper ions in the electrolyte is 70g / L to 130g / L and any value therebetween or a range between any two values, for example, 75g / L, 80g / L, 85g / L, 90g / L, 95g / L, 100g / L, 110g / L, 120g / L. When the copper ion concentration is within this range, electrolysis can be performed at a high current density to improve the electrolysis efficiency. When the copper ion concentration is high, copper sulfate is easily precipitated. When the copper ion concentration is low, the electrolyte conductivity is low, the current density is also reduced, and the electrolysis efficiency is low.
[0083] During the preparation of the electrolyte, the source of copper ions may be metallic copper, such as copper wire, copper plate, etc., and the metallic copper may be further dissolved in a sulfuric acid solution to form a sulfuric acid-copper sulfate solution.
[0084] In some embodiments, the concentration of sulfuric acid in the electrolyte is 80g / L to 150g / L and any value therebetween or a range between any two values, for example, 90g / L, 100g / L, 110g / L, 120g / L, 130g / L, 140g / L. A higher concentration of sulfuric acid increases the corrosion capacity of the equipment, which reduces the service life of the equipment. At the same time, the solubility of copper sulfate in the electrolyte decreases, and it is easy to crystallize at the edge of the electrolytic cell, and even crystallization of the pipeline causes blockage. When the concentration of sulfuric acid is low, the electrolysis efficiency is affected. The concentration of sulfuric acid within this suitable range is more conducive to electroplating.
[0085] In some embodiments, the mass concentration of halogen ions (including chloride ions, bromide ions, iodide ions, etc.) in the electrolyte is 15 mg / L to 50 mg / L and any value therebetween or a range between any two values, for example, 20 mg / L, 25 mg / L, 30 mg / L, 35 mg / L, 40 mg / L, 45 mg / L. Under low pH conditions of acid copper plating, chloride ions are adsorbed on the cathode copper with a high coverage rate, with the preferred adsorption surface being the (111) surface, and in the process of thickening the copper layer, chloride ions can continue to move to the surface position, and the adsorbed Cl -It does not hinder the deposition of copper, and can even attract copper ions and serve as a channel for electron transfer. During the electrodeposition process, chloride ions can be adsorbed on specific surfaces of crystal growth, affecting the crystal growth behavior and crystal properties, causing changes in surface morphology, and contributing to grain refinement. In addition, chloride ions are easily reduced by the cathode and Cu + Coordinate to form CuCl, and CuCl has different effects at different potentials. Generally, when the potential is positive, although Cl - With Cu + Coordination energy promotes Cu 2+ / Cu + However, the formed CuCl insoluble passivation film will be adsorbed on the cathode surface, inhibiting the conversion of Cu + / Cu conversion, thus showing a strong inhibitory effect on copper electrodeposition. When the potential is more negative, the passivation film dissolves rapidly and Cu + -Cl - The chlorine bridge effect of the complex is enhanced, catalyzing Cu + / Cu is further electro-reduced and deposited, and chloride ions act as promoters for electrodeposition.
[0086] During the preparation of the electrolyte, the halogen ion source may be HX, NaX or KX, wherein X is a halogen ion.
[0087] In some embodiments, the concentration of the organic additive in the electrolyte is 20 mg / L-500 mg / L and any value therebetween or a range between any two values, for example, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 110 mg / L, 120 mg / L, 130 mg / L, 140 mg / L. When chloride ions are used alone as additives, the performance of the copper foil obtained is relatively unstable. Chloride ions can be combined with other organic additives to act as a chloride bridge. For example, the Cu formed by chloride ions + -Cl - The ligand can provide binding sites for the adsorption of ether bonds in polyether compounds. Because of its negative charge, it is easy to have electrostatic interaction with positively charged nitrogen-containing compounds, and it is easy to form an adsorption barrier layer on the cathode surface. For example, chloride ions can combine with organic sulfides and copper ions to form bridges, accelerate material transfer, and increase Cu 2+ If the chloride ion concentration is too low, the synergistic effect with the organic additives is weak, which is not conducive to improving the mechanical strength of the copper foil; if the chloride ion concentration is too high, nodular copper particles will appear on the surface of the copper foil, affecting product performance.
[0088] In some embodiments, organic additives include levelers, brighteners, and wetting agents.
[0089] In some embodiments, the leveling agent is a nitrogen-containing compound, optionally including one or more of collagen, gelatin, thiourea, allylthiourea, ethylenethiourea and 2-amino-4-methylbenzothiazole. The mass concentration of the leveling agent in the electrolyte includes but is not limited to 0.1 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, and 40 mg / L. The leveling agent can improve the tensile strength and elongation of the electrolytic copper foil.
[0090] In some embodiments, the brightener is an organic divalent sulfide, optionally including one or more of polydisulfide propane sulfonate sodium (SPS), N,N-dimethyl-dithiocarboxamide propane sulfonate sodium (DPS), 3-mercaptopropane sulfonate sodium (MPS), 3-(benzothiazole-2-mercapto) propane sulfonate sodium (ZPS) and isothiourea propane sulfonic acid inner salt (UPS). The mass concentration of the brightener in the electrolyte includes but is not limited to 0.1 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L.
[0091] In some embodiments, the wetting agent is a polyether compound, optionally including one or more of polyethylene glycol, hydroxyethyl cellulose, polypropylene glycol, allyl polyethylene glycol and fatty amine polyoxyethylene ether. The mass concentration of the wetting agent in the electrolyte includes but is not limited to 1 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, and 40 mg / L. The wetting agent can improve the leveling and wettability of the copper deposit layer. After being added, it can increase the dispersion ability of copper ions, eliminate pinholes in the copper plating layer, and make the grains of the plating layer uniform, fine and compact.
[0092] In some embodiments, the temperature of the electrolyte during the electrolysis process is 45°C to 60°C.
[0093] In some embodiments, the electrolyte flow rate during electrolysis is 30-60 m 3 / h.
[0094] In some embodiments, the anode is a titanium plate having an iridium-tantalum coating on its surface.
[0095] In some embodiments, the cathode is a cathode roller, and its material may be high-purity titanium.
[0096] In some embodiments, the method further comprises the step of passivating the electrolytic copper foil in a passivation solution. Optionally, the passivation solution contains one or more of a chromium source, glucose and a nitride.
[0097] Furthermore, in some embodiments, the method further comprises one or more steps of stripping the copper coating from the cathode, washing, drying, and coiling.
[0098] In addition, the secondary battery and the electric device of the present application will be described as appropriate below.
[0099] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0100] Positive electrode
[0101] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0102] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0103] In some of the embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art.
[0104] It should be noted that the secondary battery of the present application may be a lithium ion battery or a sodium ion battery.
[0105] As a non-limiting example of a lithium-ion battery, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates of olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide (such as LiCoO2), lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and its modified compounds. Non-limiting examples of lithium-containing phosphates of olivine structure may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.8 Co 0.15 Al 0.05 O2.
[0106] As the sodium ion active material, at least one or more of the following materials may be included: at least one or more of sodium transition metal oxides, polyanionic compounds and Prussian blue compounds. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0107] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. A non-limiting example of the sodium transition metal oxide may be NaxMO2, where M may include one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.
[0108] As a non-limiting example of a sodium ion battery, the positive electrode active material may include one or more of the following materials: one or more of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0109] In some of these embodiments, the positive electrode active material layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0110] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0111] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt% to 80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000 to 25000 mPa·s. When the positive electrode slurry is applied, the coating unit surface density based on dry weight (excluding solvent) can be 15 to 35 mg / cm 2 The compaction density of the positive electrode sheet can be 3.0 to 3.6 g / cm3 , can be selected as 3.3~3.5g / cm 3 .
[0112] Negative electrode
[0113] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0114] In the present application, the negative electrode current collector adopts the electrolytic copper foil of the first aspect of the present application or the electrolytic copper foil prepared by the method of the second aspect of the present application. In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more. In other embodiments, the negative electrode active material is metallic lithium or a lithium alloy, such as lithium foil. Compared with traditional copper foil, the electrolytic copper foil of the present application as a negative electrode current collector can greatly enhance the bonding force with lithium foil.
[0115] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0116] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0117] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0118] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt% to 60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s to 10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75g / m 2 ~220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8g / cm 3 .
[0119] Electrolytes
[0120] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid, and the electrolytic copper foil of the present application is particularly suitable for batteries with all-solid electrolytes.
[0121] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0122] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0123] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, ), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethylene carbonate One or more of fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0124] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0125] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0126] Isolation film
[0127] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0128] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0129] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.
[0130] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0131] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0132] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0133] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.
[0134] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0135] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape.
[0136] In some embodiments, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly through a winding process or a lamination process. The electrode assembly is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly. The number of electrode assemblies contained in the battery cell can be one or more, and those skilled in the art can select according to actual needs.
[0137] The secondary battery may be a battery module or a battery pack.
[0138] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.
[0139] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0140] In addition, the present application also provides an electrical device, which includes a secondary battery provided by the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.
[0141] As an electrical device, a secondary battery can be selected according to its usage requirements.
[0142] As an example, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the secondary battery, a battery pack or a battery module may be used.
[0143] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0144] Example
[0145] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0146] Example 1
[0147] 1) Preparation of cathode electrical insulation shielding point
[0148] A direct molding method is used to prepare electrically insulating shielding points with a rectangular array on the surface of a rotating cathode roller. The electrically insulating shielding points are circular, that is, a=b=160μm, A=B=500μm, and the electrically insulating material is an ultraviolet light curing material.
[0149] 2) Electrolysis
[0150] A copper wire with a copper content of 99.99% is dissolved in sulfuric acid to form a sulfuric acid-copper sulfate solution, and then an organic additive and hydrochloric acid are added and stirred evenly to obtain an initial electrolyte. The electrolyte is filtered using a filter with a filtration accuracy of less than 0.5 μm to obtain a pure electrolyte. A cathode roller is used as the cathode, and a titanium plate with an iridium-tantalum coating on the surface is used as the anode. The anode and the cathode are separated by the electrolyte, and the cathode and cathode pole distance is 8 mm.
[0151] The concentration of sulfuric acid in the electrolyte is 115 g / L, the concentration of copper ions is 85 g / L, the concentration of chloride ions is 20 mg / L, the concentration of sodium polydisulfide propane sulfonate is 12 mg / L, the concentration of isothiourea propane sulfonic acid inner salt is 4 mg / L, the concentration of polyethylene glycol (molecular weight 4000-6000) is 15 mg / L, the concentration of collagen is 5 mg / L, and the current density is 7000 A / m 2 , prepare porous copper foil with a thickness of 6 μm, the electrolyte temperature is 50 °C, and the electrolyte flow rate is 40m 3 / h.
[0152] The cathode roller rotates at a constant speed, and the copper in the solution is deposited on the surface of the cathode roller to form copper foil. The thickness of the copper foil is controlled by the cathode current density and the speed of the cathode roller. Those skilled in the art can use conventional methods to control the current density and the speed of the cathode roller to obtain the target thickness of the copper foil. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, washed, passivated, dried, and coiled to form electrolytic copper foil.
[0153] The SEM image of the array area of the electrolytic copper foil prepared in this embodiment is as follows: Figure 3 As shown, the finished roll sample is as follows Figure 4 shown.
[0154] Example 2
[0155] 1) Preparation of cathode electrical insulation shielding point
[0156] A direct molding method is used to prepare electrically insulating shielding points with a rectangular array on the surface of a rotating cathode roller. The electrically insulating shielding points are circular, that is, a=b=300 μm, A=B=800 μm, and the electrically insulating material is an ultraviolet light curing material.
[0157] 2) Electrolysis
[0158] A copper wire with a copper content of 99.99% is dissolved in sulfuric acid to form a sulfuric acid-copper sulfate solution, and then an organic additive and hydrochloric acid are added and stirred evenly to obtain an initial electrolyte. The electrolyte is filtered using a filter with a filtration accuracy of less than 0.5 μm to obtain a pure electrolyte. A cathode roller is used as the cathode, and a titanium plate with an iridium-tantalum coating on the surface is used as the anode. The anode and the cathode are separated by the electrolyte, and the cathode and cathode pole distance is 8 mm.
[0159] The concentration of sulfuric acid in the electrolyte is 110 g / L, the concentration of copper ions is 90 g / L, the concentration of chloride ions is 25 mg / L, the concentration of sodium polydisulfide propane sulfonate is 30 mg / L, the concentration of sodium 3-(benzothiazole-2-mercapto) propane sulfonate is 15 mg / L, the concentration of polyethylene glycol (molecular weight 4000-6000) is 9 mg / L, the concentration of hydroxyethyl cellulose is 4 mg / L, the concentration of thiourea is 3 mg / L, and the current density is 6500 A / m 2 , prepare porous copper foil with a thickness of 6 μm, electrolyte temperature 53 °C, electrolyte flow rate 45m 3 / h.
[0160] The cathode roller rotates at a constant speed, and the copper in the solution is deposited on the surface of the cathode roller to form copper foil. The thickness of the copper foil is controlled by the cathode current density and the speed of the cathode roller. Those skilled in the art can use conventional methods to control the current density and the speed of the cathode roller to obtain the target thickness of the copper foil. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, washed, passivated, dried, and coiled to form electrolytic copper foil.
[0161] Example 3
[0162] 1) Preparation of cathode electrical insulation shielding point
[0163] A direct molding method is used to prepare electrically insulating shielding points with a rectangular array on the surface of a rotating cathode roller. The electrically insulating shielding points are circular, that is, a=b=400μm, A=B=1000μm, and the electrically insulating material is an ultraviolet light curing material.
[0164] 2) Electrolysis
[0165] A copper wire with a copper content of 99.99% is dissolved in sulfuric acid to form a sulfuric acid-copper sulfate solution, and then an organic additive and hydrochloric acid are added and stirred evenly to obtain an initial electrolyte. The electrolyte is filtered using a filter with a filtration accuracy of less than 0.5 μm to obtain a pure electrolyte. A cathode roller is used as the cathode, and a titanium plate with an iridium-tantalum coating on the surface is used as the anode. The anode and the cathode are separated by the electrolyte, and the cathode and cathode pole distance is 8 mm.
[0166] Among them, the sulfuric acid concentration in the electrolyte is 110g / L, the copper ion concentration is 90g / L, the chloride ion concentration is 28mg / L, the sodium polydisulfide propane sulfonate concentration is 45mg / L, the N,N-dimethyl-dithiocarboxamide propane sulfonate concentration is 28mg / L, the polyethylene glycol (molecular weight 4000-6000) concentration is 7mg / L, the hydroxyethyl cellulose concentration is 2mg / L, the collagen concentration is 1mg / L, the 2-amino-4-methylbenzothiazole concentration is 4mg / L, and the current density is 6500A / m 2 , prepare porous copper foil with a thickness of 6 μm, electrolyte temperature 53 °C, electrolyte flow rate 45m 3 / h.
[0167] The cathode roller rotates at a constant speed, and the copper in the solution is deposited on the surface of the cathode roller to form copper foil. The thickness of the copper foil is controlled by the cathode current density and the speed of the cathode roller. Those skilled in the art can use conventional methods to control the current density and the speed of the cathode roller to obtain the target thickness of the copper foil. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, washed, passivated, dried, and coiled to form electrolytic copper foil.
[0168] Example 4
[0169] 1) Preparation of cathode electrical insulation shielding point
[0170] A template method is used to prepare electrically insulating shielding points with a rectangular array on the surface of a rotating cathode roller. The electrically insulating shielding points are circular, ie, a=b=500 μm, A=B=1000 μm, and the electrically insulating material is an ultraviolet light curing material.
[0171] 2) Electrolysis
[0172] A copper wire with a copper content of 99.99% is dissolved in sulfuric acid to form a sulfuric acid-copper sulfate solution, and then an organic additive and hydrochloric acid are added and stirred evenly to obtain an initial electrolyte. The electrolyte is filtered using a filter with a filtration accuracy of less than 0.5 μm to obtain a pure electrolyte. A cathode roller is used as the cathode, and a titanium plate with an iridium-tantalum coating on the surface is used as the anode. The anode and the cathode are separated by the electrolyte, and the cathode and cathode pole distance is 8 mm.
[0173] Among them, the sulfuric acid concentration in the electrolyte is 105g / L, the copper ion concentration is 92g / L, the chloride ion concentration is 28mg / L, the 3-mercaptopropane sulfonate sodium is 50mg / L, the N,N-dimethyl-dithiocarboxamide propane sulfonate sodium concentration is 20mg / L, the polyethylene glycol (molecular weight 4000-6000) concentration is 5mg / L, the hydroxyethyl cellulose concentration is 6mg / L, the collagen concentration is 3mg / L, the 2-amino-4-methylbenzothiazole concentration is 10mg / L, and the current density is 7000A / m 2 , prepare porous copper foil with a thickness of 6 μm, electrolyte temperature 55 °C, electrolyte flow rate 45m 3 / h.
[0174] The cathode roller rotates at a constant speed, and the copper in the solution is deposited on the surface of the cathode roller to form copper foil. The thickness of the copper foil is controlled by the cathode current density and the speed of the cathode roller. Those skilled in the art can use conventional methods to control the current density and the speed of the cathode roller to obtain the target thickness of the copper foil. After the copper foil is transferred out of the liquid with the roller, it is continuously peeled off from the cathode roller, washed, passivated, dried, and coiled to form electrolytic copper foil.
[0175] Example 5
[0176] It is basically the same as Example 4, except that A=B=800 μm.
[0177] Example 6
[0178] It is basically the same as Example 1, except that a=b=400 μm.
[0179] Example 7
[0180] It is basically the same as Example 3, except that a=b=500 μm, A=B=500 μm.
[0181] Example 8
[0182] It is basically the same as Example 2, except that a=b=600 μm and A=B=500 μm.
[0183] Comparative Example 1
[0184] It is basically the same as Example 1, except that the electrical insulating shielding point is not prepared at the cathode.
[0185] Test Section
[0186] 1) Tensile strength and elongation test of electrolytic copper foil
[0187] According to the test method GB / T29847-2013, the tensile strength and elongation of the electrolytic copper foil were tested at a strain rate of 0.8 mm / s and room temperature (about 25°C) using the HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd. The tensile test specimen was a strip specimen with a total length of 100 mm and a width of 15 mm. The sample was measured three times and the average value was taken as the final tensile strength and elongation of the sample.
[0188] 2) Coulomb efficiency
[0189] Half-cell assembly and testing: The test was performed by assembling a CR2032 button cell. The assembly of the cell was completed in an argon-protected glove box. The electrolytic copper foil prepared in Examples 1 to 8 was used as the working electrode, the lithium sheet was used as the counter electrode, and the commercially available electrolyte and diaphragm were assembled into a half-cell. The CT-3008W5V20A-TF high-precision battery performance test system was used for constant current charge and discharge testing. The constant current charge and discharge test was performed at 1 mA / cm 2 The half-cell was cycled for 200 cycles at a current density of , and the final coulombic efficiency was calculated.
[0190] 3) Cycle capacity retention rate 1
[0191] Full battery 1 assembly and testing: 90 parts of commercially available silicon-carbon negative electrode active material, 4 parts of conductive agent, and 6 parts of binder were mixed in high-purity water by weight to prepare a slurry. Then, the slurry was evenly applied to the smooth surface of the electrolytic copper foil prepared in Examples 1 to 8 using a coater, and then the slurry was dried in an oven. Then, the slurry was evenly applied to the rough surface of the electrolytic copper foil prepared in Examples 1 to 8 using a coater, and then the slurry was dried in an oven. After drying, a roller press was performed. Then, the obtained negative electrode plate was assembled with a commercially available electrolyte (1 mol / L LiPF6 in EC-DEC (volume ratio 1:1)), a separator, and a positive electrode plate to manufacture a CR2032 button battery. The CT-3008W5V20A-TF high-precision battery performance test system was used for constant current charge and discharge test. The battery was charged and discharged 100 times at a rate of 1C. The cycle capacity retention rate of the battery after 100 cycles was tested. The cycle capacity retention rate indicates the percentage of the battery capacity after the final cycle discharge number to the battery capacity after the first discharge.
[0192] 4) Cycle capacity retention rate 2
[0193] Assembly and testing of full battery 2: In an inert gas argon environment, 20 μm thick lithium foils were placed on the smooth and rough surfaces of the electrolytic copper foils prepared in Examples 1 to 8, respectively. The lithium foils were composited with the copper foils by rolling, and the copper-lithium composite foils were used as the negative electrode, and the commercial positive electrode sheet was used as the positive electrode to assemble a full battery. The battery specification was CR2032, and the electrolyte used was a sulfide solid electrolyte. The CT-3008W5V20A-TF high-precision battery performance test system was used for constant current charge and discharge tests. The battery was charged and discharged 100 times at a rate of 1C, and the cycle capacity retention rate of the battery after 100 cycles was tested.
[0194] 5) Wettability test
[0195] By weight, 90 parts of commercially available silicon-carbon negative electrode active material, 4 parts of conductive agent, and 6 parts of binder are mixed in high-purity water to prepare slurry. Next, the slurry is evenly applied to the smooth surface of the electrolytic copper foil prepared in Examples 1 to 3 using a coater, and then the slurry is dried in an oven. Then, the slurry is evenly applied to the rough surface of the electrolytic copper foil prepared in Examples 1 to 3 using a coater, and then the slurry is dried in an oven. After drying, the slurry is rolled to obtain a pole piece.
[0196] The wetting behavior of the electrolyte on the electrode was tested using the Data-physics OCA 20 contact angle / surface tension meter. The contact angle after the electrolyte was dropped onto the electrode surface for 1 second indicated the wetting effect. The smaller the contact angle, the faster the electrolyte can fully wet the electrode, allowing the negative electrode active material to fully contact the electrolyte. + Providing fast transportation channels to enable Li + Faster intercalation and deintercalation in active materials.
[0197] The above test results are shown in Table 1 below:
[0198] Table 1
[0199]
[0200] The above test results show that the electrolytic copper foil provided in the present application can improve the wettability of the electrolyte, and can also improve the coulombic efficiency and cycle capacity retention rate of the battery. The coulombic efficiency and cycle capacity retention rate can characterize the strength of the adhesion between the negative electrode active material and the copper foil current collector. As a negative electrode current collector, it is particularly suitable for solid-state batteries.
[0201] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.
[0202] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A novel electrolytic copper foil, characterized in that: The invention comprises at least one copper layer, wherein at least part of the surface of the copper layer is provided with a through-hole array, wherein the through-hole array is formed by M*N through-holes arranged in M rows and N columns, M≥1, N≥1, M and N are both positive integers, each row of through-holes in the through-hole array is arranged along the x-direction, each column of through-holes in the through-hole array is arranged along the y-direction, the x-direction intersects the y-direction and is located in the same plane, the thickness direction of the copper layer is the z-direction, and the z-direction is perpendicular to both the x-direction and the y-direction; The thickness of the copper layer is recorded as h, the longest distance from the center point of the through hole to the edge of the through hole is the major semi-axis distance, and its length is recorded as a, the shortest distance from the center point of the through hole to the edge of the through hole is the minor semi-axis distance, and its length is recorded as b, the shortest vertical distance between adjacent through holes along the x direction is recorded as A, and the shortest vertical distance between adjacent through holes along the Y direction is recorded as B, the Y direction is perpendicular to the x direction, the surface area of the copper layer covered by the through hole array is the array area, and the surface area of the copper layer not covered by the through hole array is the non-array area, and the weight of the array area per square meter is recorded as m, then: Wherein, k is any value between 0.9 and 1.
1.
2. The electrolytic copper foil according to claim 1, characterized in that: A is 200-2000 μm, optionally 400-1500 μm, and / or B is 200-2000 μm, optionally 400-1500 μm.
3. The electrolytic copper foil according to claim 1, characterized in that: a is 100-1500 μm, optionally 200-1000 μm, and / or b is 100-1500 μm, optionally 200-1000 μm.
4. The electrolytic copper foil according to claim 1, characterized in that: The porosity of the array region is 5%-50%, and can be optionally 10%-40%.
5. The electrolytic copper foil according to claim 1, characterized in that: The through hole array is arranged in a rectangular array and / or a diamond array.
6. The electrolytic copper foil according to claim 1, characterized in that: The through hole is circular and / or elliptical.
7. The electrolytic copper foil according to claim 1, characterized in that: The copper layer has two surfaces opposite to each other in its thickness direction, the two surfaces are respectively a first surface and a second surface, and the first surface and the second surface have different surface roughness and / or brightness.
8. The electrolytic copper foil according to claim 1, characterized in that: The copper layer has a thickness of 3 μm-15 μm.
9. The electrolytic copper foil according to any one of claims 1 to 8, characterized in that: The tensile strength of the array area of the copper layer at room temperature is 15 kgf / mm 2 -30kgf / mm 2 The tensile strength of the non-array area of the copper layer at room temperature is 30kgf / mm 2 -70kgf / mm 2 , the room temperature is 25±5℃.
10. A method for preparing an electrolytic copper foil according to any one of claims 1 to 9, characterized in that: The steps include: The anode and the cathode to be plated are placed in an electrolyte for electrolysis to obtain an electrolytic copper foil, wherein the cathode has electrically insulating shielding points arranged in an array.
11. The method according to claim 10, characterized in that The electrolyte comprises copper ions, sulfuric acid, halogen ions and organic additives; Optionally, the concentration of the copper ions in the electrolyte is 70 g / L-130 g / L; Optionally, the concentration of sulfuric acid in the electrolyte is 80 g / L-150 g / L; Optionally, the concentration of the halogen ions in the electrolyte is 15 mg / L-50 mg / L; Optionally, the concentration of the organic additive in the electrolyte is 20 mg / L-500 mg / L.
12. The method for preparing an electrolytic copper foil according to claim 11, characterized in that: The organic additives include leveling agents, brighteners and wetting agents, The leveler is a nitrogen-containing compound, optionally including one or more of collagen, gelatin, thiourea, allylthiourea, ethylenethiourea and 2-amino-4-methylbenzothiazole, and optionally the mass concentration of the leveler in the electrolyte is 0.1 mg / L-40 mg / L; and / or, The brightener is an organic divalent sulfide, optionally including one or more of sodium polydisulfide propane sulfonate, sodium N,N-dimethyl-dithiocarboxamide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium 3-(benzothiazole-2-mercapto) propane sulfonate and isothiourea propane sulfonic acid inner salt, and optionally the mass concentration of the brightener in the electrolyte is 0.1 mg / L-400 mg / L; and / or, The wetting agent is a polyether compound, optionally including one or more of polyethylene glycol, hydroxyethyl cellulose, polypropylene glycol, allyl polyethylene glycol, and fatty amine polyoxyethylene ether. Optionally, the mass concentration of the wetting agent in the electrolyte is 1 mg / L-40 mg / L.
13. The method for preparing an electrolytic copper foil according to claim 10, characterized in that: The temperature of the electrolyte during the electrolysis process is 45°C-60°C.
14. A negative electrode plate, characterized in that: The invention comprises the electrolytic copper foil according to any one of claims 1 to 9, and the electrolytic copper foil prepared according to any one of claims 10 to 13.
15. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 14.
16. The secondary battery according to claim 15, characterized in that: The secondary battery is a liquid, semi-solid or solid battery.
17. An electrical device, characterized in that: Comprising at least one of the secondary batteries described in claim 16.
Citation Information
Patent Citations
Preparation process for copper foil for lithium ion battery current collector
CN102931414A
Porous composite foil, positive pole piece, negative pole piece, semi-solid lithium ion battery and preparation method
CN115832195A
Battery composite pole piece and preparation method thereof
CN116581235A
Anti-edge-tearing production method of electrolytic copper foil and electrolytic copper foil for lithium ion battery
CN118028912A
Production method of double-sided roughened porous electrolytic copper foil
CN118256961A
Cited By
Porous copper foil and preparation method and application thereof
CN121407162A
Porous current collector, pole piece, battery and preparation method
CN122025660A